(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article is devoted to the analysis of the ideological factor in the 1916 anti-colonial uprising of the Kyrgyz people, examined within the context of the worldview of the Zamanist poets (de-modernists) of the 19th and early 20th centuries. The purpose of the study is to identify the role of the «Zamanist» ideology as a form of intellectual and spiritual resistance to the colonial modernization of the Russian Empire, and to determine its influence on the formation of the protest consciousness of Kyrgyz society on the eve of the 1916 events. The 1916 uprising is considered not merely as a reaction to colonial pressure, but also as a manifestation of a profound ideological conflict between the imperial modernization project and the traditional worldview of the nomadic society